TOURISM AREA DEVELOPMENT PLANNING USING SWOT ANALYSIS IN MEDAN LABUHAN DISTRICT AS A NATURAL RESERVE AREA AND CULTURAL HERITAGE - Feby Milanie; Dimas Setiawan; Febby Khafilwara; Syafri Benta; Ardiles Hasianta; Gusti Elcitra Limbong (RADJA PUBLIKA, 2024)
Tourism is a potential source of local income, and can enhance a city's identity. Tourism in an area is of good value, it will also accelerate the development of that area. This acceleration can be achieved when the level of visits to the area increases and will ultimately increase economic activity. In order to maximize making a city a tourist destination, the city government must be able to recognize the physical and non-physical potential of the city. This potential can be maximized so that a city can become a tourist destination with its own characteristics, whether it is natural tourism, historical tourism or cultural tourism. According to the Medan City RTRW for 2010-2030, it is stated that the old city center area of ​​Medan Labuhan District is a Nature Reserve and Cultural Heritage Area. Therefore, this study focuses on the concept of tourism in Medan Labuhan District. This study uses a subjective method with an inventory approach and identification of potential and related problems, analysis and ultimately providing strategic recommendations and regional planning plans.